1979
DOI: 10.7164/antibiotics.32.379
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the biosynthesis of the antibiotic streptozotocin (streptozocin) by Streptomyces achromogenes var. streptozoticus. Feeding experiments with carbon-14 and tritium labelled precursors.

Abstract: Feeding experiments and chemical degradations have shown that D-[l-1'C,2-'H]-and-THE JOURNAL OF ANTIBIOTICS APR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…c) experiments were performed. b, Exposing SZN to UV-light generated a one-carbon and one-nitrogen labeled cyclic urea previously reported to be a denitrosated SZN product, indicating that the distal nitroso nitrogen is labeled 9 . c, MS/MS fragmentation of SZN revealed a one-carbon labeled cyclic carbamate fragment, indicating that both the N-nitroso nitrogens are labeled.…”
Section: Addition Of Superoxide Dismutase and Catalase To Sznf Reaction Mixtures-mentioning
confidence: 96%
See 1 more Smart Citation
“…c) experiments were performed. b, Exposing SZN to UV-light generated a one-carbon and one-nitrogen labeled cyclic urea previously reported to be a denitrosated SZN product, indicating that the distal nitroso nitrogen is labeled 9 . c, MS/MS fragmentation of SZN revealed a one-carbon labeled cyclic carbamate fragment, indicating that both the N-nitroso nitrogens are labeled.…”
Section: Addition Of Superoxide Dismutase and Catalase To Sznf Reaction Mixtures-mentioning
confidence: 96%
“…streptozoticus NRRL 2697 revealed the origins of the sugar scaffold (D-glucosamine), the ureido linkage (Larginine or L-citrulline), and the N-methyl group (L-methionine) (Extended Data Fig. 1a) 9 . Though N-nitroso group biosynthesis was not investigated, the distal nitroso nitrogen atom was hypothesized to come from nitrite.…”
mentioning
confidence: 99%
“…The biosynthesis of streptozotocin is hypothesized to utilize nitrous acid or a biochemical equivalent to nitrosate the corresponding urea (Scheme 50). 1 Feeding studies with radioactively labeled compounds have indicated that glucosamine, L-methionine, and either L-citrulline or L-arginine are precursors to this metabolite. Future studies will be required to address the similarities and differences of N- nitrosation mechanism in primary and secondary metabolism.…”
Section: N–n Bond Forming Enzymesmentioning
confidence: 99%
“…Microbes produce antimicrobial agents that can cause DNA damage through a variety of mechanisms, including DNA methylation by methyl halides (64), induction of single-or doublestrand breaks by bleomycin (65), inhibition of topoisomerase IV and DNA gyrase by quinolone derivatives (66), and induction of reactive oxygen species that can damage DNA by numerous antibiotics (67) and antifungals (68). Production of MNIBA by Muscodor isolates is most analogous to production of streptozotocin, a D-glucopyranose derivative of MNU, by Streptomyces achromogenes (69). Streptozotocin is a known methylating agent that is utilized as an anticancer drug that primarily targets pancreatic tumors (70).…”
Section: Discussionmentioning
confidence: 99%